233 Working towards an adaptive trial platform for Parkinson's disease. Issue 6 (27th May 2022) - Zeissler, Marie-Louise; Dominey, Thea; Morris, Huw; Bandmann, Oliver; Schrag, Annette; Foltynie, Tom; Carroll, Camille
Abstract : Background: No intervention for Parkinson's disease (PD) has been unequivocally proven to be neuro- protective. Setting up phase 2 and 3 clinical trials in isolation is costly, time consuming and inefficient. An adaptive trial design may allow streamlining clinical evaluation, with interim analyses allowing for early detection and replacement of ineffective arms. We were interested to explore the practicalities of developing an adaptive trial for PD. Method: We consulted with experts in disease areas where adaptive trials have been initiated and sought support from national and international Parkinson's experts, charities, and input from patient advocates. Results: Following consultation, we have adapted the process successfully employed by the multiple sclerosis (MS) Society in the development of the STOP MS initiative. Initial steps involve a review of recent trial methodologies and a Delphi study involving multi-organisational stakeholders, including patients and international experts. These results will inform the function of working groups responsible for drug selection, trial design, outcome measure selection and infrastructure. Conclusions: Developing a adaptive trial for PD is challenging. However, we now have a process to take this forward, building on the success of similar initiatives in other neurodegenerative diseases. marie-louise.zeissler@plymouth.ac.uk